La seguridad interna del estado (art.137 #6 LOMH) como limitante a la movilidad humana - Cárdenas Chamorro, Tamia Micaela (2019)
As a background, we should understand migration as the phenomenon that represents the essential relationship for the development of peoples. whie human mobility constítutes a universal right for all human beings. Migration and human mobility have existed since the beginning at mankind since man had to travel in search of tood and sheñer in order to survive; Today people move in search of better living conditions. The present investigation aims to demonstrato hat Art.137 K 6 of the Organic Law of Human Mobility fímits this fundamental right, violating the constitutional regulations and the internabional Treabes and Conventions ratified by Ecuador, we will conduct an explanatory descriptivo study with a systemic approach where procedures carried out by the Ombudsman's Office, the Public Defenders Office and the Ministry of Foreign Affairs and Human Mobility were reviewed in the period between October 2017 and October 2018, as well as a legal analysis of the regulations that regulate human mobility coming to the conclusion that art, 137 4 6 of the Organic Law of Human Mobility is a strategy used by the state lo aliow or deny the entry of foreigners into the country.